2016
DOI: 10.1016/j.talanta.2016.02.060
|View full text |Cite
|
Sign up to set email alerts
|

A metabolomics approach to identify and quantify the phytochemicals in watermelons by quantitative 1HNMR

Abstract: Watermelon (Citrullus vulgaris) contains many health-promoting compounds, such as ascorbic acid, carotenoids, phenolic acids and amino acids including l-citrulline, arginine, and glutathione. Reported HPLC method for quantification of l-citrulline and sugars in watermelon involves, time-consuming sample preparation, post-column color development and detection with fluorescence and refractive index detectors. The present study describes development of a method to identify and quantify amino acids and sugars sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…In continuation of our research on the rapid identification and characterization of bioactive compounds from fruit and vegetables, the present study focused on the UHPLC/HR‐ESI‐QTOFMS and SRM based structural elucidation of minor flavonoids from spinach. Extraction is a key step for obtaining the bioactive compounds from a plant matrix and previous research revealed that flavonoid‐rich extracts are best obtained from spinach by using methanol, 80% methanol, 70% methanol, or a mixture of methanol and water .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In continuation of our research on the rapid identification and characterization of bioactive compounds from fruit and vegetables, the present study focused on the UHPLC/HR‐ESI‐QTOFMS and SRM based structural elucidation of minor flavonoids from spinach. Extraction is a key step for obtaining the bioactive compounds from a plant matrix and previous research revealed that flavonoid‐rich extracts are best obtained from spinach by using methanol, 80% methanol, 70% methanol, or a mixture of methanol and water .…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our research on the rapid identification and characterization of bioactive compounds from fruit and vegetables, [31][32][33][34][35] the present study focused on the UHPLC/HR-ESI-QTOFMS and SRM based structural elucidation of minor flavonoids from spinach.…”
Section: Resultsmentioning
confidence: 99%
“…MHz and equipped with a 5-mm multinuclear inverse probe head and NM-ASC24 sample changer (Jayaprakasha and Patil, 2016). A known quantity (2-4 mg) of nanoencapsulated sample was dissolved in 525 μL DMSO-d 6 , transferred to a 5-mm NMR tube, and spectra were recorded at 25°C.…”
Section: Drug-loading and Entrapment Efficiency Of Curcuminmentioning
confidence: 99%
“…With qNMR, the quantitation of the compounds present in a complex sample can be performed in a single, rapid and nondestructive measurement. Thus, qNMR has become the method of choice for metabolome studies and quality control of complex natural samples such as foods, plants, herbal remedies, and biofluids (Jayaprakasha and Patil, 2016).…”
Section: Formulation Of Encapsulated Curcumin Characterization and Imentioning
confidence: 99%
“…It belongs to the Cucurbitaceae plant family, which originated from the African Kalahari Desert [1]. Watermelons have high content of phytonutrients and are rich in dietary antioxidants such as carotenoids (lycopene and β -carotene), polyphenolics, ascorbic acid, and significant amino acids [2]. Watermelons are usually consumed by juicing the flesh, beneficial in the prevention and improvement of health problems, such as cardiovascular diseases, erectile dysfunction, hypertension, and cancers [3].…”
Section: Introductionmentioning
confidence: 99%